Characteristics and control mechanism of nanoscale pores in lacustrine tight carbonates: Examples from the Jurassic Da'anzhai Member in the central Sichuan Basin, China. (July 2019) - Xu, Qilu; Ma, Yongsheng; Liu, Bo; Song, Xinmin; Su, Jiao; Chen, Zhangxin
Graphical abstract: Highlights: The nanoscale storage spaces of the Da'anzhai carbonates are well developed. The nanopore structure of the Da'anzhai carbonates is more complex than other rocks. The Da'anzhai nanoscale storage spaces are mainly from terrestrial minerals. The authigenic CaCO3 minerals are negatively correlated with the nanoscale pores. Weathering, salinity, climate and hydrodynamic conditions can control nanoscale pores. Abstract: Compared with the studies of nanoscale pores in shale, coal, and tight sandstone, studies associated with lacustrine tight carbonate nanoscale pores and their control mechanisms, particularly quantitative studies combining reservoir evaluation and geochemistry, remain scarce. To address this disparity, lacustrine tight carbonate samples collected from the Jurassic Da'anzhai Member in the central Sichuan Basin of China were quantitatively investigated. Similar to other unconventional reservoirs, lacustrine tight carbonate reservoirs contain well-developed intraparticle pores, interparticle pores, and micro-cracks with nanoscale storage spaces that dominate the full-scale reservoirs. The relatively small pores (3–5 nm) make a dominant contribution to the nanoscale storage space. Isotherms and hysteresis loops are Type II and Type H3, respectively, indicating wedge-shaped pores. However, the hysteresis loops indicate more dead-end pores, larger pores, and more complex microstructures than those found in other unconventional reservoirs. The mineral in lacustrine carbonate provides a link between the reservoir and the formation environment. Strong paleo-weathering, low salinity, a humid (rainy) paleo-climate and poor hydrodynamic conditions are favorable to improve the storage spaces and terrestrial mineral contents but harmful to the formation of authigenic minerals. Terrestrial minerals, including primarily quartz, clay, and dolomite, have well-developed nanoscale pores and are positively correlated with the nanoscale storage space, whereas authigenic minerals, primarily calcite, have strong cementation and filling effects and are negatively correlated with the nanoscale storage space.